Arrangement of reinforcement in variable density timber slab systems for multi-story construction. (December 2022) - Orozco, Luis; Krtschil, Anna; Skoury, Lior; Knippers, Jan; Menges, Achim
The arrangement of columns and their spacing in multi-story timber construction is restricted to rectangular grids by the production and shipping sizes of floor assemblies. This is particularly true for hollow box floor systems, for which the punctual supports must be placed at the reinforced edges of the hollow boxes. The arrangement of the columns and their spacing is thereby restricted by the production and shipping sizes of the box ceilings to rectangular grids. To overcome these design limits a new wooden box building system is developed that allows for irregular column layouts through a tailored slab interior design. This development allows for the increased applicability of timber floor systems regardless of site shape or architectural design intent. The slab interior design is dependent on occurring forces and fabrication requirements. Three methods for the internal slab layout are developed and compared: a sequential method, a structurally informed agent-based method, and a geometrically informed agent-based method that uses both a sequential and agent-based approach. The structural performance of each method is compared through the analysis of three reinforcement layouts an architectural testing setup.